INFLUENCE OF THE LEAGUE OF NATIONS STATUTE PROVISIONS ON THE INTERESTS OF NON-MEMBER STATES - Y. Sil'chenko (Russian Journal of Economics and Law)
The article presents the detailed legal analysis of the League of Nations statute provisions touching upon interests of third countries. Special attention is paid to the Articles 11, 17-20, where the unequal position of third states with member states is confirmed. The author gives examples of practical measures taken by the League of Nations for settling international conflicts. These examples prove that League of Nations was viewed, by the third states as well, as a guarantee of international peace and unbiased mediator in settling conflicts.